Common Fixed Point Theorems For Weakly Compatible Mappings Satisfying Rational Contractive Conditions - A.K. GOYAL, A.K. GOYAL (International Journal of Psychosocial Rehabilitation, 2013)
By using notions of compatibility, weak compatibility and commutativity, we prove some common fixed point theorems for six mappings involving rational contractive conditions motivated by Nesic [13] in complete metric spaces. Our work generalizes some earlier results of Fisher [1], Jeong-Rhoades [6], Kannan [11] and others.